(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The article examines the works included in the collection Tauelsizdik Kyrandary by N. Samatuly and Ә. Shaimaghambetov, which brings together documentary-detective literary works dedicated to the selfless heroism of police officers in solving serious and especially serious crimes that caused wide public resonance in the Kyzylorda region in the 1990s and 2000s. In the stories “Kyzylorda – Shymkent – ‘Nabat’,” “The Shattyk Cave,” “The Tragedy of Four Girls,” “Kyzylorda Kidnapping,” “Six Strands of Hair in the Palm,” “A Crime Solved in Six Months,” and “Demons Hunting Taxis,” real-life truth is transformed into artistic reality. This is evidenced by the preservation of the real names of officers who served in rural, district, city, and regional divisions of the internal affairs bodies, the precise indication of the place and time of events, the disclosure of crimes that shocked the public in the 1990s, and the execution of court verdicts. It is demonstrated through concrete examples that the writers aim to analyze the causes of crimes, delve into their social underpinnings, and explore moral issues at a certain level. In the stories, evil is manifested not only in the violation of social laws, but also in the brutal and terrifying transgression of moral norms formed over centuries of human existence. In detective works, the reasons are revealed why moral, psychological, criminological, and socio-economic conflicts lead to great tragedy and the loss of human life. Issues of legal protection in the work of investigators are highlighted through the search for lost property belonging to private individuals. The writers’ mastery of psychological techniques is expressed in their penetration into the inner world of each character and in the disclosure of the cause-and-effect relationships of internal and external conflicts. Key words: prose, detective, plot, clues, investigator, mysterious crime, unexpected plot twist, denouement